2012 9th IEEE International Symposium on Biomedical Imaging (ISBI) 2012
DOI: 10.1109/isbi.2012.6235474
|View full text |Cite
|
Sign up to set email alerts
|

Entropy based DTI quality control via regional orientation distribution

Abstract: Diffusion Tensor Imaging (DTI) has received increasing attention in the neuroimaging community. However, the complex Diffusion Weighted Images (DWI) acquisition protocol are prone to artifacts induced by motion and low signal-to-noise rations(SNRs). A rigorous quality control (QC) and error correction procedure is absolutely necessary for DTI data analysis. Most existing QC procedures are conducted in the DWI domain and/or on a voxel level, but our own experiments show that these methods often do not fully det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Recent studies [Hiltunen et al, 2006, Gallichan et al, 2010, Farzinfar et al, 2012, 2013b] have demonstrated a new kind of artifact that was not previously detected by DTIPrep. These artifacts manifest themselves as a strong bias in the measured principal direction of diffusion (PD).…”
Section: Methodsmentioning
confidence: 98%
See 3 more Smart Citations
“…Recent studies [Hiltunen et al, 2006, Gallichan et al, 2010, Farzinfar et al, 2012, 2013b] have demonstrated a new kind of artifact that was not previously detected by DTIPrep. These artifacts manifest themselves as a strong bias in the measured principal direction of diffusion (PD).…”
Section: Methodsmentioning
confidence: 98%
“…However, the vibration artifact presents itself either as a global disruption in the intensities or as local, gradual intensity change in neighboring slices over a subset of DWI's. To detect these artifacts, we have recently proposed a novel approach using an entropy-based measurement of the PD distribution (Farzinfar et al, 2012, 2013b). The orientation distribution is computed via a spherical histogram, using an icosahedron subdivision scheme to create the histogram bins.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The DWI-QC techniques aim to detect and correct these artifacts including inter/intra-slice intensity change [5], venetian blind [5], dropout signal intensities and vibration artifacts [6, 7] and eddy-current and motion artifacts [8, 5]; prior to tensor estimation. It is important to note that there are some pitfalls associated with these QC approaches [9] in the result of QC after correcting these artifacts.…”
Section: Introductionmentioning
confidence: 99%